Body Dissatisfaction among Young Girls in Recreational Rhythmic Gymnastics - Belén Portas Nuñez; Miguel Adriano Sanchez-Lastra; José C. Diz; Carlos Ayán Pérez (MDPI AG, 2024)
Body dissatisfaction is commonly associated with rhythmic gymnastics (RG) practice, but limited research exists on the prevalence of this issue among recreational level practitioners. This study examines body image dissatisfaction among young girls practicing RG recreationally. A total of 88 girls between six and eleven years of age, who participate in RG as an extracurricular activity, were measured and completed the Stunkard pictogram. To create a control group, 88 girls who did not practice RG were also recruited and matched to the gymnasts by age. Results revealed that the mean body mass index values in both groups were within the normal weight range. The mean score for body dissatisfaction was similar between the two groups, with slightly positive values (RG = 0.94; CG = 1.06). The Mann-Whitney U test showed that there was no significant difference in the ratings of actual body size, ideal body size, and body dissatisfaction between the RG and control groups. These findings suggest that practicing RG at a young age is not associated with body dissatisfaction among girls.